IMPROVED RESULTS PROCESSING METHODOLOGY FACTORIAL EXPERIMENT - Moisyshyn, V.M.; Ivasiutyn, A. P.; Protsiuk, V. R. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2022)
In the process of processing the results of experimental studies of any, in particular, technical processes, there is a necessity to establish a correlation between independent and dependent variables. During the analysis of experimental data, such a connection is established by using certain computer programs. The authors proposed the App program. 1 to calculate the parameters of ten empirical regression equations using the method of least squares, which is developed in the Visual Studio programming environment in the C# (Сі Sharp) programming language using the “Windows Form Application” framework using Windows operating systems. This program can be used in processing the results of studies conducted both according to the classical, and factorial (rational) plans. Making analysis data of experiments, conducted according to the factor plan with the help of this program the parameters of partial empirical dependencies of the studied factor Y on independent external factors are determined. The basic version of the method of creating an empirical multifactorial model of multiple nonlinear correlations based on the data obtained by the method of rational planning of the experiment is the version proposed in the work "Methodology of processing the results of a factorial experiment". The authors supplemented this method by determining the parameters of partial empirical dependencies based on logarithmic experimental data for averaging of which the geometric mean is used for each independent factor. It is proposed to determine the parameters of partial empirical dependencies, which are used to create a multifactorial model, based on the antilogarithms of the averaged values.